(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2026)
The article examines the influence of various finely dispersed fillers on the consumer and technological properties of footwear thermoplastic compositions obtained based on polyolefin derivatives.